ANALISIS BAURAN PEMASARAN PADA RUMAH MANASIK HIJRAH MUSLIM CENTER PAYAKUMBUH - Hidayatullah, Syarif; Ridhah, Habibatur (Institut Agama Islam Negeri Metro, 2024)
It is very important for pilgrims to explore and study the science of rituals before carrying out the Hajj or Umrah. At Rumah Manasik Hijrah Muslim Center (HMC) Payakumbuh there were fluctuations and targets were not achieved. Therefore, the research aims to analyze the implementation of the marketing mix carried out by Rumah Manasik HMC Payakumbuh which has not been carried out optimally, because it is still. This type of research includes field research using qualitative descriptive methods. The author chose a qualitative method using interviews and observations. This research uses 8 informants who will be interviewed, namely leaders, employees and several congregation members who took part in the manasik study at Rumah Manasik HMC Payakumbuh. The results of the research obtained are that the officers and sections of the manasik organizers at Rumah Manasik HMC Payakumbuh have implemented good 7P marketing, namely Product, price, promotion, place, people, physical evidence, and process. All forms of products provided by Rumah Manasik HMC Payakumbuh are certainly more affordable and will be able to help the congregation in worshiping while in the holy land. Using various methods for preaching, whether using print media, digital electronics and social media can certainly attract the interest of the congregation. Currently, the most effective marketing method carried out by Rumah Manasik HMC Payakumbuh is by conveying messages by word of mouth.